ANALISIS PENGAWASAN PADA SEKRETARIAT DAERAH KOTA BOGOR - Sari, Lena Ratna; Purnamasari, Irma; Seran, G Goris (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2018)
The background of this research is affected by the supervision conditions of Bogor Regional Secretariat employees who have not been maximized. It is shown from the inspection implementation only done twice in 2017 that is on March 27, and July 3, 2017. The research aims to find out the way of supervision carried out by the head of Bogor Regional Secretariat. This research is a descriptive research using the weight mean score. The sampling technique uses proportionate stratified random sampling with a sample of 69 people and the technique of data collecting uses questionnaires, interviews, literature studies and documentation. The results of the descriptive analysis show that the Supervision variable got a score of 3.756 belongs to good criteria.Â It can be concluded that the supervision at Bogor Regional Secretariat is in good criteria. This research suggested the head of Bogor Regional Secretariat to approach the employee and make suggestions for making decisions.Â Keywords: Supervision, Leader, Employee, Regional Secretariat, Bogor City.